Megatrends Asia : the eight Asian megatrends that are changing the world. - Naisbitt, John (N. Brealey Pub. LondonGB, 1996)
Describes the eight major shifts that are taking place in Asia such as: from nation states to networks; from export-led to consumer-driven; from Western influence to the Asian way; from government-driven to market driven; from villages to supercities; from labour-intensive to high technology; from male dominance to emergence of women; and, West to East.